PERAN DAN FUNGSI BHABINKAMTIBMAS DALAM MENCIPTAKAN SITUASI KEAMANAN YANG KONDUSIF DALAM MASYARAKAT DI KOTA PADANG PANJANG - Netrivianti, Netrivianti (Ensiklopedia of Journal, 2023)
The role of Bhabinkamtibmas in creating a conducive situation in society, namely carrying out outreach to the community, carrying out visits to the community, disseminating information about maintaining community security and order, motivating people to carry out siskamling in environmental security in community activities, implementing guidance and counseling services in solving problems -problems that occur in the community, the process of the guidance carried out by Bhabinkamtibmas in solving problems that occur in the community. It is hoped that the police, especially the Padang Panjang Police, can improve their performance in increasing public trust in the police so that a sense of security is created. It is hoped that the public, especially those in the Padang Panjang city area, can monitor and follow the course of every police performance process so that they can assess and give confidence to the police to carry out their duties.